Answer:
Step-by-step explanation:
combine like terms. not trying to be mean, but that all you have to do.
Second one if you distribute the first expression you get the second equation so the expressions are equivalent
Answer:
the second one for #4 and the third one for #5
Step-by-step explanation:
4. The sum of x and y is 24, so x+y = 24. The difference is 15, so x-y = 15, or
y-x=15 (they didn't specify which was which). Therefore, A, C, and D are correct, so x = 15-y is the answer (x = 15-y is the same as x+y = 15, which is false).
5.
Matt = 6 apple pies + 4 lemon pies and he got 80 dollars.
Ming = 6 apple pies + 5 lemon pies and he got 94 dollars.
If apple pie is "a" and lemon is "l":
6a + 4l = 80
6a + 5l = 94,
so C is the answer
Answer:
e t
Step-by-step explanation: